Meeting Report: Metabolites in Safety Testing (MIST) Symposium—Safety Assessment of Human Metabolites: What’s REALLY Necessary to Ascertain Exposure Coverage in Safety Tests? - Gao, Hongying (Springer US, 2013)
In the 2012 AAPS metabolites in safety testing (MIST) symposium held in Chicago, IL, USA, on October 15, 2012, regulatory experts and industrial scientists joined together to discuss their perspectives and strategies in addressing contemporary MIST recommendations (FDA 2008, International Conference on Harmonization (ICH) M3(R2), ICH M(R2) Q&A). Overall, these regulatory guidances indicate that metabolites identified in human plasma should circulate at similar or greater concentrations in at least one of the animal species used in nonclinical safety assessment of the parent drug. However, synthetic standards for the metabolites often do not exist or they are intractable to synthesize, thus introducing multiple challenges in drug development for the quantitative comparison of metabolites between human and animals. A tiered bioanalytical strategy for metabolite analysis is a prevalent approach to demonstrate coverage in animals. Recent developments in bioanalytical methodology have yielded several time- and resource-sparing strategies to provide fit-for-purpose approaches that can enable critical decisions related to metabolite quantification and monitoring in plasma. This report summarizes the presentations and panel discussions at the symposium.